Up-to-date literature review and issues of sedation during digestive endoscopy - Lu-Lu Lv; Meng-Meng Zhang (Videosurgery and Other Miniinvasive Techniques, 2023)
Sedation is common during digestive endoscopy to provide comfort and pain relief for patients. However, the use of sedation in endoscopy also poses potential risks, and recent issues have been raised regarding its safety and administration. This literature review paper will discuss the most recent developments in the field of sedation in digestive endoscopy, including the adverse events that might be associated with sedation and how to manage it, the legal issues associated with administration, the impact of COVID-19 on sedation practices, and sedation in special situations. It will also touch upon the current guidelines and recommendations for sedation, including the importance of patient selection and monitoring and the need for training and certification for endoscopists administering sedation. The review will also analyse studies evaluating the safety and efficacy of various sedation techniques, including propofol, midazolam, and others. It will examine the benefits and drawbacks of these agents.